Formulasi Lip Cream Ekstrak Etanol Biji Buah Pinang (Areca catechu L.) sebagai Pewarna Alami - Alma Farah Lutfiyani; Satwika Budi Sawitri; Ahyana Fitrian (University Of Darussalam Gontor, 2022)
Natural dyes are a dye that can be produced from various types of plants that produce natural colors that can be obtained from existing parts in plants such as leaves, fruit, stem, flowers and seeds. Lip cream is one of the decorative cosmetics used to lubricate lips so that it is not easily dry and cracked. Lip Cream as a lip dye that can be used safely with the dye of areca nut extract (Areca catechu L.). Pinang fruit seeds as natural dyes contain Tanins and phenolic compounds. This study aims to determine the characteristics and stability of areca nuts (Areca catechu L.) as a natural dye in a lip cream preparation. In making lip cream there are several ingredients used in it such as Bees Wax, Whith Wax, Cethyl Alcohol, Dimeticone, Kaolin, Castrol Oil, Titanium Dioxide, Kaolin, Toko, and Methil Paraben. Researchers used BUA Pinang seed extract as a natural dye in a lip cream preparation with a concentration of 15%, 25%, 50%, and tested physical quality, namely organoleptic test, pH, homogeneity, and for its effectiveness, namely attachment, and the power of spread, as well as Stability test. Based on research and results of evaluation tests on the field of lip cream fruit seed extract areca nut all formulations are not significantly different in the evaluation of stability.